Analisis Dampak Nilai Tukar dan Volatilitasnya terhadap Ekspor Indonesia - Muhammad Saman Al Farid; Ryan Juminta Anward (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to explain how the impact of the exchange rate and its volatility on exports in Indonesia. The analysis technique used is Generalized Autoregressive Conditional Heteroskedasticity (GARCH) to obtain exchange rate volatility, and Vector Error Correction Model (VECM) to identify factors that affect exports. The results of the study show that in the long run, the consumer price index and exchange rate volatility have a significant impact on exports in Indonesia.